al-Sahib ibn 'Abbad, promoter of rational theology : two Mu'tazili kalam texts from the Cairo Geniza - Madelung, Wilferd.; Schmidtke, Sabine.; ʻAbd al-Jabbār ibn Aḥmad al-Asadābādī, -1025.; Ṣāḥib al-Ṭālqānī, Abū al-Qāsim Ismāʻīl ibn ʻAbbād, 936-995. (Islamic History and Civilization, 2016)
The volume contains critical editions of the extant parts of two hitherto unknown theological works by the Būyid vizier al-Ṣāḥib born ʿAbbād (d. 385/925), who is well known to have vigorously promoted the teaching of Muʿtazilī theology throughout Būyid territories and beyond. The manuscripts on which the edition is based come from Cairo Geniza store rooms. They consist of two manuscripts for each of the two texts-testimony to the impact of al-Ṣāḥib's education policy on the contemporaneous Jewish community in Cairo. The longer treatise of al-Ṣāḥib of circa 350/960, possibly his Kitāb Nahj al-sabīl fī uṣūl al-dīn , appears to be the earliest Muʿtazilī work preserved among the Jewish community. The second, briefer treatise also contains a commentary by ʿAbd al-Jabbār al-Hamadānī (d. 415/1025).